(untitled) (GEON Journal (Management, Organizations and Business), 2016)
In this paper, we present some perspectives of Integrated Marketing Communications (IMC) concept over the last decades, highlighting the IMC as a core of brand communications, taking into account that technology and consumer, customers and companies joined together. In the late 1980s the formal concept of IMC was describe, but thirty years later the principle is under construction and continues to gain widespread attention around the world. The review of the literature on IMC suggests that there is no consensus on the definition and more research is necessary to consolidate its theoretical foundations. The new holistic view of marketing behavior invites us to think about different ways to achieve synergies between members of the companies and not only in the strategy like an operative process that seeks to drive all brand messages and it contribute to increase brand equity.